Cartier, Champlain, and the Fruits of the New World: Botanical Exchange in the 16th and 17th Centuries - Dickenson, Victoria (Scientia Canadensis, 2008)
AbstractMuch has been written of the Columbian exchange, the transfer between New World and Old of people, pathogens, flora and fauna. The biota of two hemispheres, once seemingly irredeemably separated, were interpenetrated, both through accident and through human agency. Part of this exchange involved medicinal and food plants, discovered in the New World and adopted into the Old. This paper examines the translation of a number of New World plants that were part of the 'Cartierian' or 'Champlinian' exchange that followed the voyages to North America by Jacques Cartier (1491-1557) between 1534 and 1541, and the explorations and settlements undertaken by Samuel de Champlain (1580?-1635) from 1603 to his death at Quebec in 1635. During this period, a number of North American plants were propagated in European nurseries and even found their way into everyday use in gardens or kitchens. How were these new plants viewed on their introduction and how were they incorporated into Europe's "vegetable" consciousness? Where did these new plants fit in the classification of the edible and the exotic?